Do Platform Switching Together with Subcrestal Placement have a Benefit on Marginal Bone Levels Around Dental Implants? - KURU, LEYLA; AĞRALI, ÖMER BİRKAN (AVES PRESS LTD, 2018)
Objective: The aim of this retrospective study was to assess the marginal bone levels around platform-switched dental implants placed subcrestally in partially or totally edentulous patients who had been treated in a private practice. Methods: A total of 200 implants placed in 64 patients, with a mean follow-up time of 5.3 +/- 1.7 years, were included in the study. Implants were placed 0.5 mm subcrestally via one-or two-stage surgical approach. Data regarding the distribution and diameter of the implants, the type of the prosthetic restoration, and marginal bone levels were assessed by one calibrated examiner. Results: Overall, the mean marginal bone loss was found to be 0.82 +/- 1.6 mm, and 66% of the implants (n=81) showed no bone loss, whereas 28% (n=35) showed bone loss >1mm, and 20% (n=25) showed bone loss >2mm. Out of 18 implants in use for 1-3 years, 14 of them showed no bone loss. Among implants that were in function for 3-5 years, 25% (n=15) showed bone loss >1mm, and 12% (n=7) showed bone loss >2mm. In this study, the majority of the implants were in use for more than 5 years (n=122). Out of them, 66% (n=81) showed no bone loss, whereas 28% (n=35) showed bone loss >1 mm, and 20% (n=25) showed bone loss >2mm. Conclusion: Within the limits of this retrospective study, one can say that slight amount of marginal bone loss is observed around the platform-switched implants placed subcrestally in a long-term follow-up. However, further studies are needed to confirm this finding.
Keywords: Bone level; dental implant; platform switch; subcrestal placement; FOLLOW-UP; PREVALENCE; SURVIVAL; DISEASES; SUCCESS; SURGERY; TRIAL